MiR-129-5p influences the progression of gastric cancer cells through interacting with - Lei Yan; Kai Sun; Yang Liu; Jun Liang; Kerui Cai; Jinqiu Gui (Tumor Biology, 2017)
The purpose of our study is to clarify the effect of microRNA-129-5p in the progression of human gastric cancer cells by regulating SPOCK1 . The expression of microRNA-129-5p and SPOCK1 was tested by quantitative real-time polymerase chain reaction in tissues and cell lines. We validated the targeted relationship between microRNA-129-5p and SPOCK1 by dual luciferase reporter gene assay. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, colony formation, flow cytometry, transwell, and wound scratch assays were used to analyze the effects of microRNA-129-5p on SGC-7901 cell viability, proliferation, cell cycle and apoptosis, invasiveness, and migration. MicroRNA-129-5p was downregulated while SPOCK1 was upregulated in gastric cancer tissues and cell lines. The result of luciferase reporter gene assay demonstrated that microRNA-129-5p can target SPOCK1 by binding to the 3′untranslated region. The overexpression of microRNA-129-5p or the inhibition of SPOCK1 inhibited SGC-7901 viability, proliferation, migration, and invasion while promoted cell cycle arrest in G0/G1 stage and cell apoptosis. Our results suggested that microRNA-129-5p could directly specifically suppress SPOCK1 , which might be one of the potential mechanisms in inhibiting cell processes including viability, proliferation, cell mitosis, migration, and invasiveness of gastric cancer cells.